2020
DOI: 10.29210/02598jpgi0005
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Faktor-faktor yang Mempengaruhi Relasi Kuasa Pelaku Kekerasan dalam Rumah Tangga (KDRT)

Abstract: <span lang="IN">Cases of violence in Indonesia, especially against women in the household, have increased so that it is considered quite alarming. Domestic violence perpetrated by the perpetrator, in this case the husband, is motivated by power relations in the household. This research aims to analyze the factors that influence the power relations of domestic violence (KDRT).The method used in this research is a descriptive qualitative approach with the research subject, namely a criminal case of domesti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
0
2
0
1
Order By: Relevance
“…These patriarchal values specifically segregate parenting roles as well as domestic duties. This is often the justification for men to domesticate women, because it is considered that women only work for domestic needs (Syawitri, 2020). Despite the fact that women are often associated with negative stereotypes, several studies have shown that women have high resilience abilities in dealing with disaster situations that threaten their survival.…”
Section: Anthropogenic Disaster Climate Crisis and Patriarchymentioning
confidence: 99%
See 1 more Smart Citation
“…These patriarchal values specifically segregate parenting roles as well as domestic duties. This is often the justification for men to domesticate women, because it is considered that women only work for domestic needs (Syawitri, 2020). Despite the fact that women are often associated with negative stereotypes, several studies have shown that women have high resilience abilities in dealing with disaster situations that threaten their survival.…”
Section: Anthropogenic Disaster Climate Crisis and Patriarchymentioning
confidence: 99%
“…McNamara (2020) shows that there is still gender violence that comes from poor market security and is experienced by female traders, and on the other hand, he also says that the source of vulnerability for women is based on factors of poverty and inequality. Poverty is related to family economic conditions, while inequality is related to the different treatment received by men and women in a society that still has a patriarchal ideology (Syawitri, 2020). Jewett, Mah, Howell, and Larsen (2021) present their recent findings regarding the linkage of social cohesion and community resilience as important resources in recovery after any disaster.…”
Section: Dukungan Masyarakat Dan Ketersediaan Sumber Dayamentioning
confidence: 99%
“…Kekerasan ini dapat juga muncul dalam hubungan pacaran, atau dialami oleh orang yang bekerja membantu kerjakerja rumah tangga dan menetap dalam rumah tangga tersebut. Selain itu, KDRT juga dimaknai sebagai kekerasan terhadap perempuan oleh anggota keluarga yang memiliki hubungan darah (Syawitri & Afdal, 2020).…”
Section: Analisis Situasionalunclassified